PENGARUH FRAUD TRIANGLE DAN ETIKA TERHADAP POTENSI PLAGIARISME MAHASISWA PRODI AKUNTANSI (STUDI KASUS DI LP3I BANDUNG) - Lilis Saidah Napisah; Yulianto Dirdjosumarto (JRAK (Jurnal Riset Akuntansi dan Bisnis), 2018)
Corruption and dishonest behavior often encountered on the newspaper, magazines or online media. Fraud and ethical violations also not only occur in the government and private sectors but also in the environment of ivory tower or academic environment. Fraud at the higher educative institutions or at the university is better known as academic cheating (academic dishonesty). Academic fraud is one types of frauds. One mode of academic fraud is plagiarism. Plagiarism done by students who hold D3, S1, S2, and also S3 and plagiarism also happened not only in Indonesia but also in other countries. The reasons of plagiarism can be seen from various aspects such as aspects of technological development and communication, culture, lacking of reading, depressed by time and activity, lack of sanctions for plagiarists, misunderstanding the meaning of plagiarism and various other aspects or factors. Plagiarism or the potential for plagiarism can be analyzed from the fraud triangle (motive, opportunity, and rationalization) and ethics. The purpose of this study is to prove whether fraud triangle and ethics can influence the potential of accounting student’s plagiarism. The usefulness of research is to improve quality of student, to create the reliability of final assignment, to prepare of final assignment book on the basis of ethics, to improve the compliance with internal regulations of LP3I Polytechnic, to maintain the good image of LP3I Polytechnic. The research conducted by the author can be classified as applied research, survey research, and associative research. The research methodology used by writer is descriptive method in which objects of the research can be analyzed and interpreted. The samples of this research are 100 students among 250 students who have been preparing final assignments at Bandung LP3I Polytechnic. Primary data were obtained through observation, interview, and using questionnaires. The validity of data was tested by implementing construct validity. The reliability of data was tested by implementing the Cronbach Alpha. The data obtained were processed using SPSS 20 software with multiple linear regression model. According to simultaneous hypothesis, the final results of the research show that fraud triangle (X1) and ethics (X2) influence significantly the potential of accounting student’s plagiarism. Based on partial hypothesis, fraud triangle (X1) influences significantly the potential of accounting student’s plagiarism and ethics (X2) influences significantly the potential of accounting student’s plagiarism